(untitled) (GAIMS Journal of Medical Sciences, 2023)
A Medical Practitioner after obtaining the required qualifications gets registered with the respective State Medical Council or the National Medical Council. If the person is registered with a State Medical Council and shifts his practice to another state, he has to re-register with the other state after obtaining No-Objection-Certificate from his previously registered Medical Council. When a Medical Practitioner applies for a job or vacancy position, along with filling the application form, one also has to submit all required documents, right from school certificates to post-graduation degrees. This application process becomes cumbersome particularly when one has to apply for multiple positions and that too in a short period of time. A Centralized Medical Registration System which is updated timely by the candidate and verified by the Registration Agency can serve as a great tool for both the recruiters and the candidates. There are international services like ECFMG, ERAS and EPIC which provide a registration and verification process for the candidate in exchange for a fee. The candidate while applying for a position has to just share his registration ID with the portal and the recruiter can access the profile of the candidate. It becomes the responsibility of the applicant to keep the profile updated with timely addition of newly acquired qualifications, certifications and work-experiences.